The Fundamental Question of Philosophy in the Historical-Philosophical Context - Openkov , Mikhail Yuryevich; Tetenkov , Nikolay Borisovich (Journal of Ecohumanism, 2025)
This article focuses on the relativization of the so-called “fundamental question of philosophy.” In Marxist philosophy, this question was considered eternal and immutable. However, it was formulated by F. Engels within the context of the 19th-century scientific revolution. Following Engels' logic and his positivist approach, each scientific revolution brings modifications to the fundamental question. The same occurred during the quantum revolution when the fundamental question shifted to the status of reality and methods of studying it. A productive discussion between Einstein and Bohr significantly advanced the understanding of physical reality and its exploration. The EPR (Einstein-Podolsky-Rosen paradox) thought experiment effectively introduced the concept of a quantum communication channel, forming the basis for the next scientific revolution: the revolution in quantum computing. Philosophy is proposed to play a more elevated and meaningful role than merely serving as an intellectual janitor. Instead, philosophy can act as a scout, charting the intellectual landscape that physics may later inhabit. Furthermore, the concept of quantum artificial intelligence emerges. It necessitates developing an acceptable understanding of consciousness and intelligence and determining the basis of human consciousness—whether it is rooted in logic or something deeper that we tend to overlook. Until these questions are resolved, the issue of Artificial Intelligence will remain a philosophical pseudoproblem. Thus, the modern formulation of the fundamental question of philosophy becomes: What is consciousness? How can this phenomenon be adequately studied?